2015
DOI: 10.1007/s10151-015-1369-3
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of pilonidal disease: guidelines of the Italian Society of Colorectal Surgery (SICCR)

Abstract: The Italian Society of Colorectal Surgery (SICCR.) has prepared clinical practice guidelines to help its members to optimize the treatment of pilonidal disease, a very common condition, especially among young people, and therefore of great importance on a socioeconomic level. The SICCR committee of experts on pilonidal disease analyzed the international literature and evaluated current evidence. Nonoperative management includes gluteal cleft shaving, laser epilation as well as fibrin glue and phenol injection:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
9

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 72 publications
2
55
1
9
Order By: Relevance
“…In previous reports, it has been suggested that factors such as male gender, obesity, sitting for a long time, repeated trauma to the sacrococcygeal region, excessive body hair, poor hygiene, and smoking have been reported to be associated with increased rates of complications after pilonidal sinus surgery . In our study, no significant difference was found between the two groups in terms of gender and smoking.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In previous reports, it has been suggested that factors such as male gender, obesity, sitting for a long time, repeated trauma to the sacrococcygeal region, excessive body hair, poor hygiene, and smoking have been reported to be associated with increased rates of complications after pilonidal sinus surgery . In our study, no significant difference was found between the two groups in terms of gender and smoking.…”
Section: Discussioncontrasting
confidence: 54%
“…However, an observation has been made that these studies advocating the application of antibiotics have different results. For example, in a study in which systemic antibiotherapy was applied, the use of clindamycin for 2 weeks did not show a significant difference in the recovery rate in primary closure procedures, whereas in another study, it was shown that leaving the wound open after the primary incision and using metronidazole for 14 days resulted in a moderately shorter recovery time . In another study suggesting the application of absorbable gentamycin on a surgery site, it has been shown that there is no clear improvement in recurrence rates .…”
Section: Discussionmentioning
confidence: 99%
“…• забезпечити повне вилікування епітеліального куприкового ходу з мінімальним ризиком рецидивів; • бути простою; • вимагати невеликих термінів госпіталізації; • давати найменший ризик ускладнень; • гарантувати швидке відновлення пацієнта [12,34,38]. Висічення епітеліального куприкового ходу з ушиванням рани наглухо.…”
Section: хірургічне лікування епітеліального куприкового ходуunclassified
“…Surgical treatment is considered the best option, with a high relapse rate (5–20%) . Other methods such as alexandrite laser (755 nm), diode laser (800 or 810 nm), intense pulsed light (IPL) or neodymium‐doped yttrium aluminium garnet (Nd:YAG) laser have been used for epilation as an adjuvant treatment after surgical intervention.…”
mentioning
confidence: 99%